Coupling of C-nitro-NH-azoles with arylboronic acids. A route to N-aryl-C-nitroazoles - Kurpet, Marta K.; Dąbrowska, Aleksandra; Jarosz, Małgorzata M.; Kajewska-Kania, Katarzyna; Kuźnik, Nikodem; Suwiński, Jerzy W. (Beilstein Journal of Organic Chemistry, 2013)
A method for the synthesis of N-aryl-C-nitroazoles is presented. A coupling reaction between variously substituted arylboronic acids and 3(5)-nitro-1H-pyrazole catalyzed by copper salt has been carried out in methanol in the presence of sodium hydroxide to afford the desired N-aryl-C-nitroazoles in good yields. This synthetic route has also been successfully applied to obtain N-phenyl derivatives of 4-nitropyrazole, 2-nitroimidazole, 4(5)-nitroimidazole and 3-nitro-1,2,4-triazole.
Keywords: arylboronic acids; C-nitroazoles; coupling; N-arylation; N-aryl-C-nitroazoles